Pediatric cancer deaths: curative or palliative? - Menon, Bina Sharine; Mohamed, Mahfuzah; Eni, Juraida; Ibrahim, Mohd Hishamshah (Mary Ann Liebert, 2008)
Aims: The aims of this study were to review the deaths of Malaysian pediatric oncology patients in order to determine the major causes and the proportion of patients who received palliative care.